Vowel reduction of English grammatical words by Macedonian EFL learners - Duckinoska, Ivana (John Benjamins Publishing Company, 2021)
Research into L2 vowel reduction shows that learners find this phenomenon challenging to acquire, most likely due to their inability to differentiate between stressed and unstressed syllables. Consequently, their L2 speech is characterised by overuse of strong forms, which may be detrimental to intelligibility. This study explores vowel reduction in grammatical words by Macedonian learners of English (N = 121). Participants at B1, B2 and C1 proficiency levels completed 25 tasks which elicited target words in spontaneous speech. The results reveal that learners predominantly use strong forms. Moreover, weak form use is significantly associated with learners’ proficiency level and formal pronunciation training, but not with word category. It was also observed that words with certain strong vowels are more frequently reduced.
Keywords: vowel reduction, strong forms, weak forms, grammatical words, language proficiency, pronunciation training